Mechanical properties of stent-graft materials - Isa C.T. Santos (2012)
An aneurysm is a localized blood-filled dilatation of an artery whose consequences can be deadly. One of its current treatments is endovascular aneurysm repair (EVAR), a minimally invasive procedure in which an endoprosthesis, called a stent-graft, is placed transluminally to prevent wall rupture. Early stent-grafts were custom designed for the patient through the assembling of off-the-shelf components by the operating surgeon. However, nowadays, stent-grafts have become a commercial product. The existing endoprostheses differ in several aspects, such as shape design and materials, but they have in common a metallic scaffold with a polymeric covering membrane. This paper aims to gather relevant information for those who wish to understand the principles of stent-grafts and even to develop new devices. Hence, a stent-graft classification based on different characteristics is presented, and the significant features of an ideal device are pointed out. Additionally, the materials currently in use to fabricate this type of prosthesis are reviewed and new materials are suggested.